1997
DOI: 10.1128/jcm.35.8.2013-2017.1997
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric detection of Cryptosporidium oocysts in human stool samples

Abstract: Cryptosporidium parvum is an important pathogen that causes diarrhea in virtually all human populations. Improved diagnostic methods are needed to understand the risk factors, modes of transmission, and impact of cryptosporidiosis. In the present study, we fluorescently labeled and counted C. parvum oocysts by flow cytometry (FC) and developed a simple and efficient method of processing human stool samples for FC analysis. Formed stool (suspended in phosphate-buffered saline) from an asymptomatic, healthy indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
19
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 18 publications
4
19
0
Order By: Relevance
“…Flow cytometry represented the most sensitive method of detection with these samples, detecting 5 ϫ 10 4 oocysts/g of fecal material, which is consistent with other reports (1,7). Flow cytometry was 10 times more sensitive than the IFA and AF techniques.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…Flow cytometry represented the most sensitive method of detection with these samples, detecting 5 ϫ 10 4 oocysts/g of fecal material, which is consistent with other reports (1,7). Flow cytometry was 10 times more sensitive than the IFA and AF techniques.…”
supporting
confidence: 90%
“…The oocyst concentration required for 100% sensitivity (5 ϫ 10 5 oocysts/g of feces) was the same for IFA and AF. The IFA did not perform as well in our study, as reported elsewhere (2,7).…”
supporting
confidence: 59%
See 1 more Smart Citation
“…99AE99-100% after a 7AE6 and 10-40 mJ cm )2 UV irradiation, respectively (Al-Adhami et al 2007;Rochelle et al 2004). In the present suckling mouse model, fluorescent flow cytometry that requires expensive set-up and technical expertise provided advantages compared with conventional fluorescence microscopy, such as higher sensitivity (10-15 times in experimentally infected SCID mice), larger test sample volumes (20-fold or more) and lower variability at low element concentrations (Valdez et al 1997;Arrowood et al 1995;Bennett et al 1999). Fluorescent cytometry was previously shown to be able to detect oocysts in samples found 'negative' using lowsensitivity fluorescence microscopy (Messner et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…For each series of experiments, a control oocyst suspension was used to verify the cytometer settings. To ensure that nonoocyst particles were removed from the data analysis, immunofluorescently stained particles were gated on a plot of side scatter vs green fluorescence data, and the area was subsequently analysed by plotting forward vs side scatter data (Valdez et al 1997, Delaunay et al 2000. Absolute oocyst counts were obtained using fluorescent calibrated beads (Fluorospheres ⁄ Flow-countÔ; Beckman Coulter, Fullerton, CA, USA).…”
Section: Immunofluorescent Flow Cytometrymentioning
confidence: 99%